iOLE—Human-Centered Software Design for Leakage Detection in Water Distribution Networks - Ivo Daniel; David Steffelbauer; Ella Steins; Jonas Schorr; Sophie Persigehl; Enrique Campbell; Johannes Koslowski; Jens Kley-Holsteg; Bernd Lindemann; Andrea Cominola (Engineering proceedings, 2024)
Leakages in water distribution networks still pose major challenges to water utilities. Despite numerous technological advances, the adoption of digital leakage detection technology remains a slow process. Here, we present the project iOLE—intelligent Online LEakage detection, where we aim to increase the applicability of automated leak detection in practice through enhanced user experience and detection robustness. iOLE employs a human-centered design approach that involves the feedback of potential users during its development process to maximize subsequent user acceptance. To this end, we design a graphical user interface, combine model-based and data-driven leakage detection, and conduct a comprehensive robustness analysis.